PEMIKIRAN EKONOMI AL-MAQRIZI BERKAITAN DENGAN KETIDAKSTABILAN POLITIK, EKONOMI, DAN MONETER PADA ERA EKONOMI KONTEMPORER - Siradjuddin; Fitri Ramdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
One of the Muslim scholars who contributed significantly to economic thought is Al-Maqrizi. Al-Maqrizi is an Islamic economic thinker who conducted in-depth studies on two important aspects, namely money and inflation. These two aspects represent issues that commonly arise in everyday economic life. The focus of this study is to examine Al-Maqrizi’s Islamic economic thought on the concept of money and the theory of inflation, as well as its application in the modern economy. This research employs a qualitative approach using library research methods. The data analysis technique applied is content analysis, with data sources derived from secondary materials, including relevant books, journals, and scholarly articles. The findings reveal that, according to Al-Maqrizi, government oversight of currency issuance and circulation is essential to prevent imbalances that may lead to inflation. Furthermore, the application of Al-Maqrizi’s ideas on money and inflation in the contemporary economic context can be seen in monetary policies aimed at preventing inflation, as well as in addressing forms of political, economic, and monetary instability in the modern era.